2015
DOI: 10.1016/j.apsusc.2014.09.172
|View full text |Cite
|
Sign up to set email alerts
|

Laser Induced Forward Transfer for front contact improvement in silicon heterojunction solar cells

Abstract: a b s t r a c tIn this work the Laser Induced Forward Transfer (LIFT) technique is investigated to create n-doped regions on p-type c-Si substrates. The precursor source of LIFT consisted in a phosphorous-doped hydrogenated amorphous silicon layer grown by Plasma Enhanced Chemical Vapor Deposition (PECVD) onto a transparent substrate. Transfer of the doping atoms occurs when a sequence of laser pulses impinging onto the doped layer propels the material toward the substrate. The laser irradiation not only trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…The laser-induced forward transfer (LIFT) method is well developed, as described in a recent review article by Serra et al (Serra and Piqué 2019). Colina et al (2015) demonstrated the laser-induced forward transfer technique to create n-doped regions on p-type c-Si substrates. The laser processing not only transferred the doping material but also produced localized heating for enhanced diffusion of the dopant.…”
Section: Laser-induced Forward Transfer (Lift)mentioning
confidence: 99%
“…The laser-induced forward transfer (LIFT) method is well developed, as described in a recent review article by Serra et al (Serra and Piqué 2019). Colina et al (2015) demonstrated the laser-induced forward transfer technique to create n-doped regions on p-type c-Si substrates. The laser processing not only transferred the doping material but also produced localized heating for enhanced diffusion of the dopant.…”
Section: Laser-induced Forward Transfer (Lift)mentioning
confidence: 99%
“…Μια εφαρμογή με πολύ μεγάλο βιομηχανικό ενδιαφέρον, στην οποία η τεχνική LIFT μπορεί να παίξει σημαντικό ρόλο, είναι η κατασκευή φωτοβολταϊκών. Η τεχνική LIFT έχει προταθεί για την δημιουργία περιοχών υψηλού ντοπαρίσματος στο μπροστινό [79] και στο πίσω [80] μέρος μίας ηλιακής κυψελίδας. Οι περιοχές αυτές, οι οποίες εκτυπώθηκαν από δότες άμορφου πυριτίου ντοπαρισμένου με φώσφορο, μειώνουν την σειριακή αντίσταση της κυψελίδας.…”
Section: εκτύπωση ηλεκτρονικών με την τεχνική Liftunclassified
“…for the transference of nanocomposite films through a small gap and kept in contact (Sakata et al, 2005). 2021), phosphor (Ferré et al, 2011;Colina et al, 2015) and antimony (Hoffmann, Röder and Köhler, 2012) have already been transferred as dopants by LTD techniques. Laser Molecular Implantation (LMI), sometimes referred to as Laser-Induced Molecular Implantation (LIMIT), allows the selective implantation of fluorescent molecules into a polymer film (Fukumura, Kohji and Masuhara, 1996), even in complex patterns such as typographic letters (Goto, Masahiro et al, 2004), or multifunctional organic molecular devices (Goto, Masahiro et al, 2004).…”
Section: Laser-induced Thermal Imaging (Liti)mentioning
confidence: 99%